2017
DOI: 10.1016/j.molmet.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and eIF2α phosphorylation: The Achilles heel of pancreatic β cells

Abstract: BackgroundPancreatic β cell dysfunction and death are central in the pathogenesis of most if not all forms of diabetes. Understanding the molecular mechanisms underlying β cell failure is important to develop β cell protective approaches.Scope of reviewHere we review the role of endoplasmic reticulum stress and dysregulated endoplasmic reticulum stress signaling in β cell failure in monogenic and polygenic forms of diabetes. There is substantial evidence for the presence of endoplasmic reticulum stress in β ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 195 publications
4
188
0
4
Order By: Relevance
“…EM studies on pancreatic sections of human subjects with T2D showed marked enlargement of the β‐cell ER . Histological analyses of pancreatic sections from patients with T1D and T2D and from animal models of diabetes showed dysregulation of different UPR makers, including sXBP1, phosphorylated eIF2α, ATF3, ATF6, CHOP and chaperones, for example, p58 IPK and BiP . Part of the UPR markers (ATF3, CHOP and BiP) were increased in both T1D and in T2D, whereas other markers (phosphorylated eIF2α and ATF6) seem to be decreased .…”
Section: Proinsulin Misfolding Er Function and Stress In Common Formmentioning
confidence: 99%
See 2 more Smart Citations
“…EM studies on pancreatic sections of human subjects with T2D showed marked enlargement of the β‐cell ER . Histological analyses of pancreatic sections from patients with T1D and T2D and from animal models of diabetes showed dysregulation of different UPR makers, including sXBP1, phosphorylated eIF2α, ATF3, ATF6, CHOP and chaperones, for example, p58 IPK and BiP . Part of the UPR markers (ATF3, CHOP and BiP) were increased in both T1D and in T2D, whereas other markers (phosphorylated eIF2α and ATF6) seem to be decreased .…”
Section: Proinsulin Misfolding Er Function and Stress In Common Formmentioning
confidence: 99%
“…In human β‐cells, the expression of different UPR genes and chaperones is high, suggesting that β‐cells are well equipped to cope with rapid fluctuations in proinsulin synthesis and with the generation of misfolded proteins . When activation of the UPR fails to correct protein folding, it may eventually lead to apoptosis, a process called “terminal UPR.” The latter is mediated via stress kinases, such as JNK and transcription factors including CHOP/GADD153 and ATF3 .…”
Section: β‐Cell Adaptation To Proinsulin Misfoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of STZ to rats at the end of week 2 leads to a sharp significant increase in the level of FPG in diabetic groups (week 3) compared to their respective normal controls received only the citrate buffer. During the remaining experimental period (weeks [4][5][6][7][8][9][10][11][12][13][14], the level of nonfasting plasma glucose (NFPG) was significantly lower in UDCA-treated groups than that of DM group. At the end of the experimental period (week 15), FPG levels were significantly ameliorated in both UDCA-treated groups compared to DM group, however, they are still recording significant differences compared to NC animals ( Figure 1a).…”
Section: Induction Of Diabetes and Body Weight Changesmentioning
confidence: 99%
“…This might explain why insulin secretion was increased after A2aR activation in TM-treated MIN6 cells.Dephosphorylation of p-eIF2α is necessary to reinitiate translation of vital proteins for cell survival. During ER stress, GADD34 is overexpressed and activates protein phosphatase-1 (PP-1) to dephosphorylate p-eIF2α(Cnop, Toivonen, Igoillo-Esteve, & Salpea, 2017).…”
mentioning
confidence: 99%